HRM and performance: the vulnerability of soft HRM practices during recession and retrenchment. (November 2016) - Cook, Hugh; MacKenzie, Robert; Forde, Christopher
Abstract : This multi‐method case explores how change in HRM implementation can impact performance metrics in a recessionary climate. Qualitative HR outcome data are mapped against financial metrics to explore adoption of hard‐line HRM practices in a major UK retailer. Despite record profits throughout the recession, the organisation responded strategically to worsening conditions in the labour market, firstly to maintain operational flexibility, but then to opportunistically enlarge jobs and intensify work to help achieve immediate gains in financial metrics, including a gain of 37 per cent in profit per employee over 3 years. These gains were achieved by derailing commitment‐based approaches to HRM, pointing towards the vulnerability of soft HRM systems during times of austerity or retrenchment.